Implementation of Differentiated Instruction Strategies for Students’ Learning Motivation in Islamic Elementary School - Tutut Handayani; Ines Tasya Jadidah; Utami Milyarta Lestari; Trisna Liza; Muhammad Raihan Alfarizi; Anis Malik Toha; Yani Pratiwi; Leny Marlina (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aimed to analyze the strategies used by Islamic Education teachers in managing differentiated learning and its impacts on students’ learning motivation at Az-Zahra Islamic Elementary School, Palembang. Using a qualitative case study design, the research involved six Islamic Religious Education (IRE) teachers and students from grades 1 to 6. Data were analyzed using Miles, Huberman, and Saldana’s interactive model, which consists of three cyclical stages: data reduction, data display, and conclusion drawing/verification. This model was selected because it enables continuous interaction between the researcher and the data, allowing emerging patterns to be refined throughout the analysis process. The findings revealed that IRE teachers implemented differentiated learning through four main strategies: differentiation of content, process, product, and learning environment, each aligned with diagnostic assessment results. Teachers adapted instructional materials to address students’ diverse needs, designed varied learning activities, and developed lesson plans, modules, worksheets, and assessments that accommodated individual differences. The learning environment was also extended beyond the classroom through outdoor and experiential activities that reduced fatigue and enhanced engagement. Collectively, these practices fostered an inclusive and student-centered atmosphere that enhanced intrinsic motivation, active participation, perseverance, and self-confidence. Furthermore, the results indicated a significant overall improvement in students’ learning motivation, as reflected in their enthusiasm during class activities, willingness to ask questions, and independent efforts to understand the material beyond classroom sessions.